P118 'Medicines for Children' project: putting families and carers in the centre. Issue 6 (17th May 2019) - Zolotas, E; Sammons, H; Tuthill, D; Barker, C; Tomlin, S; Partridge, L; Rossiter, A; Osmond, V; Barham, H; Fox, A; ,
Abstract : Background: 'Medicines for Children' (MfC) is a joint initiative between the children´s charity WellChild, the Royal College of Paediatrics and Child Health and the Neonatal and Paediatric Pharmacists Group. The project aim is to provide parents and carers with reliable, accurate and accessible information about their child's medicines. Methods: In 2006, 600 parents and carers were surveyed in order to understand what information was needed. Paediatricians, pharmacists and a medical editor then liaised with WellChild to develop a leaflet template and wrote a set of pilot leaflets. The leaflet production was subsequently standardised. An eight-step process is followed including consultation with health professionals, families and carers. The leaflet library and a series of information videos has grown, with the assistance of a dedicated group of volunteer authors. Published leaflets are reviewed every three years. Access to information is free of charge. The project is funded by the 3 partner groups and not by pharmaceutical companies. Results: MfC hosts over 230 leaflets and videos. The MfC website 1 was launched in 2009. It was subsequently reviewed by parents and carers and re-developed in 2011 and 2015. MfC has users accessing the site from every country in the world. The information leaflets have been viewed over 3 million times in 2018, up from 7, 200 in 2009. In 2014, an independent audit of MfC found that over 90% of the parents surveyed thought that the leaflets had an appropriate layout and conveyed the information in lay terminology. Since 2011, MfC information leaflets have been certified by National Health Service Information Standard as providing high quality health information for the public. Conclusion: MfC is a successful and acclaimed project which provides high quality, reliable and accurate medicines information worldwide for more than a decade. Reference: https://www.medicinesforchildren.org.uk/. Disclosure(s): Nothing to disclose.